In Search of Risk Factors: The Origin and Early Stages of Cardiovascular Epidemiology - Alessandro Menotti; Paolo Emilio Puddu (Journal of Cardiovascular Development and Disease, 2024)
Based mainly on their personal experience, the authors try to describe the origin of cardiovascular disease (CVD) epidemiology and the problems and difficulties practitioners attempted to tackle and solve during the first few decades of this discipline, which started around the middle of the last century. Beyond identifying the characteristics of those who became CVD epidemiologists, a description is given of the initial structures of the involved studies, participation rates, risk factors measurements and standardization, clinical measurements and diagnostic criteria, mortality data collection and coding, data loading and analysis, plus a number of problems still unsolved at the beginning of the 2000s. Despite many obstacles, and the initial hostility of the medical–scientific establishment, CVD epidemiology represented a revolution in researching in the bio-medical field. In the end, it also affected clinical research introducing the use of the quantitative approach bound to mathematical–statistical procedures. After decades of hard work and the development of a number of innovative tools, CVD epidemiology received its deserved recognition, eventually being accepted as a reputable and independent scientific discipline. Yet, in several countries, especially those from Southern Europe, an academic recognition of CVD epidemiology is still lacking.